Descriptions of two new species of Bactrocera Macquart (Diptera: Tephritidae: Dacinae: Dacini) from the Philippines with distinct orange medial stripes on the scutum - Korneyev, Severyn V.; Leblanc, Luc; Hauser, Martin; General, David E. M.; Gaimari, Stephen D. (Zootaxa, 2024)
Two previously undescribed species of Bactrocera Macquart with distinct orange medial stripes on the scutum were collected in multi-lure traps baited with cue-lure during a fruit fly survey carried out in the Philippines in 2019. We describe Bactrocera youngi sp. n. and B. ellenriederae sp. n., both in the subgenus Bactrocera. An illustrated identification key is given for all known species of Bactrocera with orange stripes on the scutum. COI mitochondrial DNA sequences confirm that our new species are distinct from the other species with orange stripes. Additionally, B. bivittata Lin & Wang, 2005 is recorded from Thailand for the first time.